Effect of Cultural Intelligence and Knowledge Sharing on Work Performance: Job Satisfaction as a Mediator - Luthfi Ibnu Yusuf; Rostiana Rostiana; I Made Budiana (Eduvest - Journal of Universal Studies, 2024)
This study explores the role of cultural intelligence and knowledge sharing in influencing employee performance, with job satisfaction serving as a mediator. Performance is defined as the ability and achievements in completing tasks or reaching goals, and is impacted by both cultural intelligence and knowledge-sharing practices within the workplace. Cultural intelligence refers to the ability to adapt to diverse cultural environments and interact effectively with individuals from various backgrounds. Knowledge sharing encompasses the exchange of information, experiences, and expertise among employees across departments. Higher levels of cultural intelligence and knowledge sharing can enhance job satisfaction, which is a positive emotional state arising from job achievements and experiences. Employees with high job satisfaction tend to exhibit greater productivity and performance. This quantitative study utilized four questionnaires: cultural intelligence (Van et al., 2007), knowledge sharing (Lin et al., 2022), performance (IWPQ by Koopmans, 2014), and job satisfaction (original MSQ by Weiss et al., 1967). The sample comprised 116 active employees from PT X, a steam power plant in Cirebon, West Java, selected from a total of 606 employees. Findings reveal that job satisfaction mediates the relationship between cultural intelligence and employee performance, but does not mediate the relationship between knowledge sharing and performance. This study provides insights for tailoring employee management strategies based on factors such as age, position, education, cultural intelligence, and knowledge sharing, ultimately enhancing satisfaction and performance in a multicultural work environment.